2013
DOI: 10.1093/nar/gkt352
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of RNA duplexes by chemically modified triplex-forming oligonucleotides

Abstract: Triplex is emerging as an important RNA tertiary structure motif, in which consecutive non-canonical base pairs form between a duplex and a third strand. RNA duplex region is also often functionally important site for protein binding. Thus, triplex-forming oligonucleotides (TFOs) may be developed to regulate various biological functions involving RNA, such as viral ribosomal frameshifting and reverse transcription. How chemical modification in TFOs affects RNA triplex stability, however, is not well understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 67 publications
0
83
0
Order By: Relevance
“…Previous research shows that the p K a decrease toward neutral for N 3 in 2-thio U (p K a = 8.8) relative to U (p K a = 9.3) monomer (Figure 1D) may enhance, respectively, the Watson–Crick (14,54) and Hoogsteen hydrogen bonding (38). Consistently, our quantum mechanics calculations have revealed that the gas phase local p K a values for N 3 atoms decrease upon thiolation (L versus J, 2-thio T versus T and 2-thio C versus C; Supplementary Tables S2 and S3).…”
Section: Resultsmentioning
confidence: 86%
“…Previous research shows that the p K a decrease toward neutral for N 3 in 2-thio U (p K a = 8.8) relative to U (p K a = 9.3) monomer (Figure 1D) may enhance, respectively, the Watson–Crick (14,54) and Hoogsteen hydrogen bonding (38). Consistently, our quantum mechanics calculations have revealed that the gas phase local p K a values for N 3 atoms decrease upon thiolation (L versus J, 2-thio T versus T and 2-thio C versus C; Supplementary Tables S2 and S3).…”
Section: Resultsmentioning
confidence: 86%
“…13,33,8288 To investigate the effect of the loop-stem tertiary contacts on the unfolding kinetics of the T2 pseudoknot, we substituted L2 with a poly(U) loop. Elastic property studies have shown that a single-stranded RNA poly(U) chain tends to be more disordered with weaker loopstem tertiary interactions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, even though the major groove is relatively deep and narrow, an RNA double helix can accommodate a third strand in the major groove to form a modestly stable triplex (1113). In a major-groove triplex, the pyrimidine bases in the third strand recognize the sequence of the purine strand of the double helical RNA by Hoogsteen hydrogen bonding, forming U·A-U or T·A-U and C + ·G-C base triples (Figure 1A and B) (810).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have shown previously (15) that PNAs incorporating a modified neutral base thio-pseudoisocytosine (L) (Figure 1C) can recognize a Watson–Crick G-C pair in an RNA duplex by forming a Hoogsteen L·G pair with improved stability and minimized pH dependence compared to a Hoogsteen C + ·G pair (Figure 1B). The enhanced Hoogsteen L·G pair formation is presumably due to improved van der Waals interaction between the thio group in L and H8 in G, as well as base stacking and hydrogen bonding interactions (9,13,15). PNAs incorporating L-modified residues show selective binding to RNA duplexes over single-stranded RNAs, because a Watson–Crick-like G-L pair (Figure 1E) is destabilized compared to a Watson–Crick G-C pair due to the steric clash between the relatively bulky thio group in L and the amino group in G. Furthermore, PNAs show enhanced binding to RNA duplexes over DNA duplexes (9,1520).…”
Section: Introductionmentioning
confidence: 99%